THE TECHNOLOGICAL DIDACTIC KNOWLEDGE OF THE CONTENT (TPACK) IN UNIVERSITY TEACHERS. IMAGES AND MODES OF EXPRESSION IN CLASSROOM PRACTICES - Fernando Agustín S. Flores; Margarita Cristina Ortiz (Universidad Nacional del Nordeste, 2019)
We present preliminary results in the framework of the research project: "The construction of the didactic knowledge of content in experienced teachers and beginners of the National University of the Northeast. Multiple case study "; specifically around the visions that of the Technological Didactic Knowledge of the Content support professors and their complex ways of manifesting in the practices of subjects of Teachers and Degrees of the Faculty of Humanities. In this opportunity, we place the analysis in the images about the use of technologies in teaching and its effective incorporation into a specific didactic cycle. The theoretical proposal that we assume is the Model TPACK ("Technological Pedagogical Content Knowledge"). We adopt as a methodological strategy the study of multiple cases, for its construction we use the review and analysis of professional documents (CV and schedules), semistructured interviews and non-participant observation of classes. The cases are constituted by teachers of three (3) subjects. The predominance of the use of assimilative technologies (support for exposure), it shows a professional culture that has not yet managed to internalize the TPACK model in the academic unit.